Quality of service and traffic preemption for multi-protocol label switching / generalized multiprotocol label switching networks - Mohd. Warip, Mohd. Nazri (2007)
The Multi-Protocol Label Switching (MPLS) framework is used in internet service provider (ISP) and as a backbone to Internet Protocol (IP) to provide guaranteed efficient bandwidth and Quality of Service (QoS) provisioning in the network. This project seeks to investigate the QoS using DiffServ mechanism over MPLS and then compare the network performance in legacy networks. As a result, better network performance is observed with the integration of DiffServ over MPLS. DiffServ over MPLS provide the capability of the microflow traffic for each classtype in an aggregated packet stream with a LSP. Traffic preemption and resource preemption are introduced in QoS over MPLS to demonstrate that the class of traffic can be classless if MPLS setup-priority and holding-priority are pre-determined at user defined level.